2015
DOI: 10.1111/apt.13255
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fatigue in inflammatory bowel disease: comparison of three fatigue scales

Abstract: All three fatigue scales are likely to measure IBD fatigue adequately. Responsiveness to change has not been tested. Depression, poorer QoL and probably female gender are the major associations of fatigue in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Patients with inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), can have impaired quality of life as a result of depression [1], anxiety [2], and fatigue [34]. Sexual interest and satisfaction are other important aspects affecting quality of life, but it is unclear how these domains are impacted by IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), can have impaired quality of life as a result of depression [1], anxiety [2], and fatigue [34]. Sexual interest and satisfaction are other important aspects affecting quality of life, but it is unclear how these domains are impacted by IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Questions in Section 2 are scored on a 0–4 Likert scale, with the possible total score range from 0 to 120. The MFI was chosen to be used in conjunction with the newly developed IBD‐F scale, as it is the most frequently used scale to measure fatigue in IBD . It is a 20‐item self‐assessment instrument designed to measure the severity of multiple dimensions of fatigue (physical, mental and general fatigue, reduced activity and motivation).…”
Section: Methodsmentioning
confidence: 99%
“…Initial validation of the measure suggested that the questionnaire had good face and content validity, acceptable to excellent test–retest stability and a high degree of internal consistency [110]. Both sections of the IBD-F have been found to be significantly correlated with other widely utilised fatigue scales [22]. The scale was developed by conducting in-depth interviews with participants with IBD, in order to gain insight into their experience and ultimately to represent issues of specific importance to people with IBD fatigue.…”
Section: Methods and Designmentioning
confidence: 99%
“…The causes of fatigue in IBD are not well understood by either patients [27] or healthcare professionals (HCPs) [28]. Disease activity [22, 2931], anaemia [3234] and inflammation [32] have been found to be predictive of fatigue, yet there is a considerable number of IBD patients with no apparent physiological underpinnings for their fatigue [35]. Apart from a consistent relationship with disease activity, IBD-fatigue has been linked to psychosocial factors such as low mood [31, 36, 37] and sleep problems [29, 31, 37, 38].…”
Section: Introductionmentioning
confidence: 99%